Comparative Genomics Supports Sex and Meiosis in Diverse Amoebozoa. (31st October 2018) - Hofstatter, Paulo G; Brown, Matthew W; Lahr, Daniel J G
Abstract: Sex and reproduction are often treated as a single phenomenon in animals and plants, as in these organisms reproduction implies mixis and meiosis. In contrast, sex and reproduction are independent biological phenomena that may or may not be linked in the majority of other eukaryotes. Current evidence supports a eukaryotic ancestor bearing a mating type system and meiosis, which is a process exclusive to eukaryotes. Even though sex is ancestral, the literature regarding life cycles of amoeboid lineages depicts them as asexual organisms. Why would loss of sex be common in amoebae, if it is rarely lost, if ever, in plants and animals, as well as in fungi? One way to approach the question of meiosis in the "asexuals" is to evaluate the patterns of occurrence of genes for the proteins involved in syngamy and meiosis. We have applied a comparative genomic approach to study the occurrence of the machinery for plasmogamy, karyogamy, and meiosis in Amoebozoa, a major amoeboid supergroup. Our results support a putative occurrence of syngamy and meiotic processes in all major amoebozoan lineages. We conclude that most amoebozoans may perform mixis, recombination, and ploidy reduction through canonical meiotic processes. The present evidence indicates the possibility of sexual cycles in many lineages traditionally held as asexual.